Análisis del control interno del departamento de tesorería de la estación experimental tropical PICHILINGUE (INIAP) año 2010 - Donoso Porro, Rosanna Rosalina (2012)
This research project is focused on administrative internal control and its impact on the management of Private Educational Unit Abdon Calderon "UEPAC" Quevedo Canton. Period 2011, this special accounting work evaluates administrative processes used in this institution, this project also answers the question of the main research problem. Does prevents inefficient administrative procedures ensure effective business management in UEPAC? This research project consists of two segments, the first is the introduction and the second chapter in a six constitutes the body of the document. This research consists of a theoretical part and documentary or other practice. Being considered documentary because its objective was achieved with the application of existing theories and whose effects are known in the professional field, besides being considered practical because the information obtained, to achieve the stated objective was obtained directly from the scene to investigate. To develop the theoretical framework of the study analyzed each of the variables that occur as a result of the statement of the problem, thus obtaining the development of a theoretical, conceptual and legal, it was necessary to search for information in different media such as books, web pages, scientific papers and brochures, meeting the technical requirements of own technical and scientific writing. In developing the methodology of research methods were used as the inductive, deductive and analytical; as they are the most appropriate to run an administrative internal control guidance. As techniques were used: observation, survey and questionnaire that helped to obtain the results. The application of internal control questionnaires made to members of the administrative area of the UEPAC show that in the area with 75% rector, vice-rector with 59% and 67% with a direction, which represents a level of trust and medium risk, while in the inspection area shows 60%, 70% and secretary Collections with 67% having a level of trust and medium risk. Because the controls are deficient in effect caused the administrative processes in the period 2011, is that they can not meet or perform activities efficiently. The Private Education Unit Abdon Calderon has a manual administrative internal control during the period 201. Completing this research project, with appropriate conclusions and recommendations raised in Chapter V, the same as contribute adequately to the internal administration of the educational unit PARTICULAR Abdon Calderon